Uso de imagens de satélite como suporte à estimativa da demanda hídrica na sub-bacia do Rio Urucuia, MG - Silva, Lorena Santos Cordeiro da (2011)
This work aimed at estimating the demand for irrigation water it the Urucuia sub-basin, Minas Gerais state, using remote sensing data and comparing the results obtained with the water availability in the sub-basin. In order to estimate the irrigation water demand, the reference evapotranspiration was calculated using data collected at the Ground Automatic Meteorological Station (PCD) in the municipality of Santa Fé de Minas. Afterward, it was calculated the plant growth-evapotranspiration relation in the researched area. Landsat5/TM images were used to quantify and analyze the center pivots in each of the municipalities in the sub-basin in order to determine its irrigated area. The growth rates of plants were estimated using IBGE data from the year under review and the percentages obtained of such were used to estimate the irrigated area. It was considered the primary and the secondary stages of the plant development, the analyses of which were confronted with the water availability in the Urucuia sub-basin. To calculate the water required by irrigation, water application efficiencies were established for 60, 90 and 100% of attainable efficiency. The results showed that the demand for irrigation water was equivalent to 43% of the water availability in the sub-basin. Considering the water application efficiency of 100% and analyzing the crop coefficients, if the total area was to be irrigated with by applying Kc value for crop production, the irrigation water need in the sub-basin would demand 47% water. Applying the crop Kc value for plants at the initial growth stage, the demand for irrigation water would be 28%. Thus, it is possible to conclude that in the Urucuia sub-basin there is potential for irrigation development. However, it is important to consider the agricultural area suitability and the local water availability with the intention of mitigating future problems regarding the water usage.